A two-stage approach to agile pharmaceutical supply chain management with product substitutability in crises. (4th August 2019) - Roshan, Mohaddeseh; Tavakkoli-Moghaddam, Reza; Rahimi, Yaser
Highlights: Presenting a new model for the pharmaceutical supply chain (PCS) in crisis. Developing a new objective in the PSC to maximize the social satisfaction. Considering an online phase to update the plans in a case of any disruption. Considering perishability and substitutability of drugs in the mathematical model. Validating the mathematical model with a case study in Seattle, USA. Abstract: Natural disasters refer to a set of harmful incidents, which do not originate in humans and threaten human lives around the world. These incidents are usually unpredictable. While most natural disasters appear to be beyond human control, the damage they cause can be controlled significantly. This is directly related to the human pre-emptive action, in particular designing and managing an efficient and constant scheduling in order to provide the required pharmaceutical materials. This paper addresses crisis management in pharmaceutical supply chains, whose three objective functions are to minimize the network total cost, minimize the unmet demand and maximize the satisfaction of social responsibility. In addition, it considers perishability and substitutability with demand uncertainty. Furthermore, two approaches, i.e. TH and Me, are used to handle the multi-objective model and uncertainty. Finally, a case study is presented to validate the mathematical model. Graphical abstract: Image, graphical abstract